Photonics in nature and bioinspired designs: sustainable approaches for a colourful world - Vaz, Raquel (2020)
Biological systems possess nanoarchitectures that have evolved for specific purposes and whose ability to modulate the flow of light creates an extraordinary diversity of natural photonic structures. In particular, the striking beauty of the structural colouration observed in nature has inspired technological innovation in many fields. Intense research has been devoted to mimicking the unique vivid colours with newly designed photonic structures presenting stimuli-responsive properties, with remarkable applications in health care, safety and security. This review highlights bioinspired photonic approaches in this context, starting by presenting many appealing examples of structural colours in nature, followed by describing the versatility of fabrication methods and designed coloured structures. A particular focus is given to optical sensing for medical diagnosis, food control and environmental monitoring, which has experienced a significant growth, especially considering the advances in obtaining inexpensive miniaturized systems, more reliability, fast responses, and the use of label-free layouts. Additionally, naturally derived biomaterials and synthetic polymers are versatile and fit many different structural designs that are underlined. Progress in bioinspired photonic polymers and their integration in novel devices is discussed since recent developments have emerged to lift the expectations of smart, flexible, wearable and portable sensors. The discussion is expanded to give emphasis on additional functionalities offered to related biomedical applications and the use of structural colours in new sustainable strategies that could meet the needs of technological development.